Synthesis and biological evaluation of auristatin-F recombinant antibody-drug conjugates for cancer therapy - Huysamen, Allan Martin (Department of Chemistry, 2023)
This study serves as a contribution to the emerging field of antibody-drug conjugate (ADC) therapeutics, in which novel ADCs were generated and biologically evaluated for therapeutic potential and specificity towards cancer cells. SNAP-tag site-directed conjugation was employed in order to overcome the current challenges of heterogeneous ADC combination products resulting from standard conjugation methods. The SNAP-tag fusion proteins were generated using recombinant DNA technology, and incorporated antibody single-chain variable fragments (scFvs) exhibiting specificity towards the epidermal growth factor receptor (EGFR), chondroitin sulfate proteoglycan receptor (CSPG4) and CD44 receptors more highly expressed in various cancer types. The design and successful synthesis of two BG-linkers was followed by coupling to auristatin-F, a powerful microtubule poison, using both Cu(I)-catalysed cycloaddition and amide coupling chemistry. The BG-linkers each incorporated a noncleavable polyethylene glycol spacer, one of which included a dansyl fluorescent tag in order to aid in purification and characterisation. Ultimately, this study succeeded in producing two novel BG-modified ADC-precursors and various ADCs by virtue of SNAP-tag conjugation, three of which exhibited therapeutic potential following in vitro cytotoxicity assays. Cytotoxicity assays were undertaken by treating A431, SK-Mel-28, MDA-MB468, Hs578T and A2058 cell lines with ADCs generated from various scFv-SNAP fusion proteins, in which selectivity towards target receptor positive cell lines was demonstrated. Quantification of the efficacy of generated ADCs was afforded by IC50 values, resulting from dose-response curves, which ranged from 44 nM – 180 nM. Collectively, insights were gained into the subtleties governing the interface of molecular and macromolecular chemistry that will facilitate further research into the development of ADC cancer therapeutics.